Peran Aplikasi “Visiting Jogja” dalam Mengembalikan Kepercayaan Wisatawan untuk Berwisata ke Yogyakarta - Fitria Jalaluddin; Alfelia Nugky Permatasari (Sekolah Vokasi, Universitas Gadjah Mada, 2021)
Covid-19 made several countries adopt lock-down policies as an effort to break the chain of spreading the virus. However, this policy greatly affects sectors related to the daily mobility of people, especially the tourism sector which has been most significantly affected by Covid-19. One of the provinces in Indonesia that has experienced a major loss in the tourism sector due to Covid-19 is the Yogyakarta Special Region (DIY). Therefore, the DIY government gradually continues to encourage the tourism sector to resume operations, one of which is by releasing new applications for tourists, namely